2008
DOI: 10.1159/000171070
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nitric Oxide Donor Molsidomine on Skeletal Muscle Damage in a Rat Hind Limb Model of Ischemia-Reperfusion

Abstract: Background: In this experimental study, we aimed to examine the protective effect of molsidomine (MS), a nitric oxide (NO) donor, against ischemia-reperfusion (I-R) injury in a rat skeletal muscle model. Methods: Ischemia was achieved by application of an elastic rubber band as high as possible on the left thigh of the rats. Group 1: the control group received a sham operation. Group 2: the I-R group received I-R injury to the left hind limbs. Group 3: the I-R/MS group underwent the same model of I-R injury an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Interestingly, follistatin-like-1 cDNA administration in a nondiabetic CLI mouse model promotes endothelial cell function and stimulates revascularization in response to ischemic insult through its ability to activate Akt-eNOS signaling [ 63 ]. Therefore, follistatin administration, or other antimyostatin approaches such as decorin, antibodies against myostatin, myostatin propeptide, or shRNA against myostatin [ 60 , 64 66 ] may be investigated as ancillary treatments to improve the effects of MDSC and other stem cell implantation for the treatment of CLI in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, follistatin-like-1 cDNA administration in a nondiabetic CLI mouse model promotes endothelial cell function and stimulates revascularization in response to ischemic insult through its ability to activate Akt-eNOS signaling [ 63 ]. Therefore, follistatin administration, or other antimyostatin approaches such as decorin, antibodies against myostatin, myostatin propeptide, or shRNA against myostatin [ 60 , 64 66 ] may be investigated as ancillary treatments to improve the effects of MDSC and other stem cell implantation for the treatment of CLI in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic cross-clamping during bypass grafting in patients with abdominal aorta aneurysms (AAA) leads to development of ischemia-reperfusion injury. Previous studies have shown that increased production of reactive oxygen species (ROS), such as superoxide anions, hydroxyl radicals, or hydrogen peroxide, plays a major role in cellular damage during post-ischemic reperfusion [ 1 , 2 ]. Free radicals can participate in reduction-oxidation reactions, initiate lipid oxidation, degrade nucleic acids and membrane proteins, and increase endothelial adhesion molecule synthesis.…”
Section: Introductionmentioning
confidence: 99%